Formas diferenciais - Perucchi, Mateus Navarro [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In this work, studies aimed at evaluating the unification of concepts and theorems of vector analysis that contributed to the understanding of physical problems in a more comprehensive and more concise than using vector calculus. We study the electrodinamics with differential forms. Were also presented Maxwell's relations with formalism of differential forms in addition allowing formulation one more geometric and generalized. Another feature observed during the study of formalism presented was the possibility of it serving as a substitute to the tensor formalism

Neste trabalho, os estudos visaram avaliar a unificação de conceitos e teoremas de análise vetorial que contribuíram na compreensão de problemas físicos de maneira mais abrangente e muito mais concisa do que usando o cálculo vetorial. Estudamos a eletrodinâmica com formas diferenciais. Foram também apresentadas as relações de Maxwell com o formalismo das formas diferenciais permitindo além da formulação axiomática da Termodinâmica uma mais geométrica e generalizada. Outra característica observada durante o estudo do formalismo apresentado foi a possibilidade dele servir como substituto ao formalismo tensorial
Keywords: Fisica matematica; Formas diferenciais; Termodinamica; Maxwell, Equações de; Eletrodinamica